Approximal Attrition and Permanent Tooth Crown Size in a Romano-British Population - A. H. Brook; C. Underhill; L. K. Foo; M. Hector (Dental Anthropology Association, 2006)
The aim was to measure mesiodistal crown size of both sexes in different age groups of a well characterised Romano-British population to determine the progressive effects of approximal attrition. From the collection in the British Museum of Romano-British skeletons excavated from Poundbury, aged and sexed by Museum staff on established criteria, two samples were selected randomly from those with intact permanent dentitions. The first examiner measured the teeth of 30 males and 30 females aged 14-24 years and the second examiner those of 59 males and 51 females distributed across the four age groups, namely 14-24, 25-34, 35-45, over 45 years. The mesiodistal diameter of each permanent tooth was measured on two separate occasions and the mean for each tooth type in each age group calculated. Differences were explored with two sample t-tests and multiple regression analysis. The intra-operator reproducibility for difference tooth types ranged from r = 0.92 to r = 0.99 and for inter-operator reproducibility from r = 0.74 to r = 0.99. In the youngest age group males had larger teeth than females with this difference being statistically significant for most tooth types. There was a pattern of decreasing tooth size over the four age groups, with males more affected than females. Different tooth types showed different reductions, the greatest being in upper and lower incisors and upper first molars and the least in lower second molars, upper second molars and third molars. The average total arch length reduction estimated by two different methods between aged groups 1 and 4 was 10.0mm in the upper jaw and 6.4 mm in the lower jaw. Thus, in this Romano-British sample all tooth types showed reduction in mesiodistal diameter with increasing age, the extent varying between the sexes, the jaws and tooth types. From comparable studies, this approximal attrition was slightly greater than for mediaeval Swedes and considerably greater than modern Swedes and other Caucasians.